La sociedad en nombre colectivo y su incidencia ante la Personalidad Jurídica requerida para el manejo de las sociedades, en la intendencia de Compañías y valores del Cantón Ambato, en el año 2014. - Bravo Galárraga, Christian Sebastián (2016)
The research work aim is to analyze the legal personality incidence within the company in the collective name for the management required by the super intendance of values companies, since the aforementioned company infringe upon what is the legal representation so that all partners are fully responsible for all that of their actions. The first chapter starts treating what is the legal entity, from which come the words etymologically, concept, its legal characterization which is the civil code article 564 'legal person is called a fictitious person capable of exercising rights and contract civil obligations, and be represented in judicial and extrajudicial'. The second chapter explains what society is, when it was born in the world and in Ecuador, the background of the mercantile society in the middle ages and in modern times in the country; society characteristics, by removing differences between what is a civil society and a company each with its respective classification. The third chapter introduces the collective name society its concept, characteristics, if it is appointed in shaping what would be its administrator, powers, limitations and responsibilities of managers in the company, which is the responsibility, solidary, subsidiary, limited; reaching the legal foundation of the society in collective name within our legislation with their respective concordances. The fourth chapter presents the terms of collective name society, which represents the judicial and extrajudicial representation, and its legal basis within the law of companies. The fifth chapter leads on society in collective name and its incidence in the presentation of the legal person, and the problems that cause the lack of representation in collective name society. The complete research has been necessary, in the same degree that we studied the theoretical and legal part, doing some field research to substantiate this work about the criterion by means of an interview with the administration of company’s attorney and values of the Ambato canton, in the same way their opinions through lawyers’ surveys to independent legal representatives.